B=5a-4
pick any a valve and replace it with a you will get b
![3(14 - 5x) = 16 - 12x](https://tex.z-dn.net/?f=3%2814%20-%205x%29%20%3D%2016%20-%2012x)
Distribute 3 throught the parentheses
![42 - 15x = 16-12x](https://tex.z-dn.net/?f=42%20-%2015x%20%3D%2016-12x)
Move the variable to the left-hand side and change its sign
![42 - 15x + 12x = 16](https://tex.z-dn.net/?f=42%20-%2015x%20%2B%2012x%20%3D%2016)
Move the constant to the right-hand side and change its sign
![- 15x+12x=16 - 42](https://tex.z-dn.net/?f=%20-%2015x%2B12x%3D16%20-%2042)
Collect like terms
![- 3x = - 26](https://tex.z-dn.net/?f=%20-%203x%20%3D%20%20-%2026)
Divide both sides of the equation by -3
![\boxed{x = \frac{26}{3} }](https://tex.z-dn.net/?f=%20%5Cboxed%7Bx%20%3D%20%20%5Cfrac%7B26%7D%7B3%7D%20%7D)
Answer: FIRST OPTION
Step-by-step explanation:
To solve this problem you must apply the Intersecting Secant-Tangent Theorem. By definition, when a secant line and a tangent lline and a secant segment are drawn to a circle from an exterior point:
![(Tangent\ line)^2=(Secant\ line)(External\ Secant\ line)](https://tex.z-dn.net/?f=%28Tangent%5C%20line%29%5E2%3D%28Secant%5C%20line%29%28External%5C%20Secant%5C%20line%29)
The total measure of the secant shown is:
![18+Diameter](https://tex.z-dn.net/?f=18%2BDiameter)
If the radius is 7, then the diameter is:
![D=7*2=14](https://tex.z-dn.net/?f=D%3D7%2A2%3D14)
Therefore:
![Secant\ line=18+14=32](https://tex.z-dn.net/?f=Secant%5C%20line%3D18%2B14%3D32)
You also know that:
![External\ Secant\ line=18\\Tangent\ line=x](https://tex.z-dn.net/?f=External%5C%20Secant%5C%20line%3D18%5C%5CTangent%5C%20line%3Dx)
Keeping the above on mind, you can substitute values and solve for x:
![x=\sqrt{576}\\x=24](https://tex.z-dn.net/?f=x%3D%5Csqrt%7B576%7D%5C%5Cx%3D24)
the answer is A ,when x=0,g(x)is-1,so when u add x into the g(x),which is given below,u can find C,D,E,g(x) is no equal to -1,when you add x=1 into g(x)(A,B),you can find g(x) of B is 0,which is no equal the answer giving above(g(x)=2),but A is all right.